Sustainable marketing mix and SMEs’ sustainability: The mediating role of competitive advantage - Novalensiago, Monica; Christiani, Natalia (Jurnal Manajemen Bisnis dan Kewirausahaan, 2025)
SMEs’ sustainability has become a strategic priority amid increasing business uncertainty. This study examines the effect of the Sustainable Marketing Mix, including Sustainable Product, Sustainable Price, Sustainable Place, Sustainable Promotion, and Sustainable People, on SMEs’ Sustainability, with Competitive Advantages as a mediating variable. Focusing on building material retail businesses in Riau Province, Indonesia, data from 156 respondents, including customers and potential customers, were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that Sustainable People and Sustainable Place significantly influence both Competitive Advantages and SMEs’ Sustainability, while Sustainable Product affects SMEs’ Sustainability directly. Competitive Advantages significantly mediate the relationship between Sustainable People and SMEs’ Sustainability. Theoretically, this study enriches RBV-based sustainability research by identifying Sustainable People as a unique internal resource that strengthens SMEs’ sustainability both directly and through competitive advantages. Practically, SMEs are encouraged to enhance human resource capabilities and distribution efficiency, while policymakers and business associations should implement training, mentoring, and incentive programs to support sustainability-driven strategies. Future research may explore additional factors such as digital capabilities, dynamic capabilities, or entrepreneurial resilience, and adopt longitudinal or mixed-method approaches to capture evolving challenges in increasingly volatile and disruptive business environments.